Nanoparticle Platforms for Antigen-Specific Immune Tolerance - Thorp, Edward B.; Boada, Christian; Jarbath, Clarens; Luo, Xunrong (Frontiers in Immunology, 2020)
Innovative approaches in nanoparticle design have facilitated the creation of new formulations of nanoparticles that are capable of selectively calibrating the immune response. These nanomaterials may be engineered to interact with specific cellular and molecular targets. Recent advancements in nanoparticle synthesis have enabled surface functionalization of particles that mimic the diversity of ligands on the cell surface. Platforms synthesized using these design principles, called “biomimetic” nanoparticles, have achieved increasingly sophisticated targeting specificity and cellular trafficking capabilities. This holds great promise for next generation therapies that seek to achieve immune tolerance. In this review, we discuss the importance of physical design parameters including size, shape, and biomimetic surface functionalization, on the biodistribution, safety and efficacy of biologic nanoparticles. We will also explore potential applications for immune tolerance for organ or stem cell transplantation.